2015
DOI: 10.1080/13607863.2015.1114589
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of music concerts in promoting well-being in dementia care

Abstract: Objectives: This study explores the specific effects of live music concerts on the clients with dementia, their families and nursing staff / caregivers. Methods:Researchers attended 22 concerts in care facilities in England and Japan. Interviews were carried out with clients with dementia, nursing staff and family members. Observations were also carried out before, during and after the concerts. All observations were recorded in field notes. Results:The effect of the concerts in both countries were seen to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The strongest results were for improved mood and/or emotions, which were found to improve for shared music listening across all studies. Improved social interaction and communication also appeared to show consistent effects, which were particularly marked among participants with dementia, though less so for those with more severe dementia (van der Vleuten et al, 2012 ; Clements-Cortés, 2017 ; Shibazaki and Marshall, 2017 ; Toccafondi et al, 2018 ). As part of this, sharing music stimulated participants' memories and facilitated reminiscing and storytelling that were shared with musicians, staff, and family members.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The strongest results were for improved mood and/or emotions, which were found to improve for shared music listening across all studies. Improved social interaction and communication also appeared to show consistent effects, which were particularly marked among participants with dementia, though less so for those with more severe dementia (van der Vleuten et al, 2012 ; Clements-Cortés, 2017 ; Shibazaki and Marshall, 2017 ; Toccafondi et al, 2018 ). As part of this, sharing music stimulated participants' memories and facilitated reminiscing and storytelling that were shared with musicians, staff, and family members.…”
Section: Resultsmentioning
confidence: 93%
“…Synchronized movement and physical activation increased during live music sharing alongside the ability to remember, cognitively perceive, and anticipate auditory musical elements (Clements-Cortés, 2017 ; Shibazaki and Marshall, 2017 ). Participants were reported to be clapping, singing, and generally moving to the music.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Live music performances have been shown to have a positive effect on human contact, care relationships, positive emotions and negative emotions in people with dementia in nursing homes (van der Vleuten et al 2012). Shibazaki and Marshall (2017) explored the effects of live music concerts on dementia sufferers, their families, nursing staff and caregivers. Interviews and researcher attendance at concerts in care facilities showed that concerts were beneficial to patients and staff even when they did not attend the concerts.…”
mentioning
confidence: 99%
“…combat the incidence of depression and improve social participation and quality of life of older adults in long-term-care settings (Kirchen & Hersch, 2015;Shibazaki & Marshall, 2015).…”
mentioning
confidence: 99%